Enhancing oral and public health scholarship at Orapuh: Unveiling the Orapuh vocabulary - Adamu, V. E.; Eneojo, Ndidiamaka Ijeoma (Orapuh Journal, 2024)
The Orapuh Vocabulary represents a cornerstone of communication and understanding within the Orapuh community. As an international, independent organization incorporated in the Republic of The Gambia as a charity, Orapuh is committed to promoting astute scholarship, professional proficiency, and open science in the field. This conceptual paper introduces and elucidates the Orapuh Vocabulary, providing clear definitions and pronunciation guides for key terms that encapsulate the ethos, mission, and activities of Orapuh. By presenting this comprehensive lexicon, the paper aims to facilitate communication, foster collaboration, and advance knowledge in oral and public health scholarship among professionals of Orapuh extraction